PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA RODA PUTAR TERHADAP HASIL BELAJAR PPKN PESERTA DIDIK SEKOLAH DASAR - Larasati, Niken; Perdana, Dayu Rika; Nuraini, Siti; Erni, Erni (PEDAGOGIKA: Jurnal Pedagogik dan Dinamika Pendidikan, 2025)
The problem of this research is the low PPKn learning outcomes of class III students at SD Negeri 1 Metro Utara. The aim of the research is to determine the positive influence of the Teams Games Tournament (TGT) type cooperative learning model assisted by spinning wheel media on the PPKn learning outcomes of elementary school students. This type of research uses quantitative research with quasi-experimental methods and research design using non-equivalent control group design. The population of this study was 87 students and the sample was 58 students. Determination of the sample using purposive sampling technique. Data collection techniques use tests in the form of pretests and posttests and non-tests in the form of observations. Data were analyzed using simple linear regression. The results of the research are that there is an influence on the application of the Teams Games Tournament (TGT) type cooperative learning model assisted by spinning wheel media on the PPKn learning outcomes of class III students at SD Negeri 1 Metro Utara.